Wear-resistant adhesive and preparation method thereof

By using silicone resins, modified alumina, modified silica and other materials in adhesives, and processing plasma and composite silane coupling agents, the wear resistance and adhesion of existing adhesives at high temperatures is solved. The problem of insufficient bonding strength achieves efficient high temperature and wear resistance.

CN119463797AInactive Publication Date: 2025-02-18CHANGZHOU LANMAI BUILDING DECORATION MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411369944.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to develop adhesives that can maintain wear resistance and high bond strength under high temperature conditions, especially in the aerospace, aerospace and electronics industries, where adhesives need to work long-term and maintain performance at high temperatures.

Method used

Silicone resin is used as colloid, and a wear-resistant adhesive is prepared by adding modified alumina, modified silica, curing agent and reinforcement, combined with plasma and composite silane coupling agent.

Benefits of technology

It achieves the maintenance of wear resistance and high bonding strength under high temperature conditions, and is suitable for the aviation, aerospace and electronics industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067313220000091
    Figure BDA0005067313220000091
  • Figure BDA0005067313220000101
    Figure BDA0005067313220000101
Patent Text Reader

Abstract

The invention discloses a wear-resistant adhesive and a preparation method thereof, and relates to the technical field of adhesives. According to the invention, 4-phenylbutyltrimethoxysilane is utilized to modify fumed alumina and fumed silica, so that the fumed alumina and fumed silica have enhanced oleophylic properties and can be uniformly dispersed in organic silicon resin, and meanwhile, the high temperature resistance and bonding strength of a matrix are improved; the heat resistance of a matrix is improved, curing of resin colloid is promoted, the high temperature resistance and bonding strength of the colloid are improved, titanium and boron carbide are used as reinforcing agents, so that the bonding strength and the high temperature resistance of the colloid are greatly improved, then the colloid is subjected to plasma treatment and then soaked in a composite silane coupling agent, and the bonding strength and the high temperature resistance of the colloid are improved. Therefore, the adhesive force between the colloid and the base material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a wear-resistant adhesive and a preparation method thereof. Background Art

[0002] As a major category in the chemical industry, adhesives play a very important role in promoting the development of many fields in daily life with the development of functional polymer synthetic chemistry. Such as medicine, aerospace, agriculture, construction, etc. Adhesion refers to a phenomenon in which two surfaces are bonded together through the interaction between atoms or molecules. By bonding two surfaces, two objects in a separated state can withstand the transfer of force and energy through the interface. Adhesion is a complex process, and there are many factors that can affect the bonding properties of materials. The interfacial force that binds two objects together may come from van der Waals forces, hydrogen bonds, chemical bonds, and electrostatic attraction. The mechanical strength of the system depends not only on the mechanical strength of the adhesive, but also on the interaction between the adhesive and the two objects in the interface area. Compared with mechanical fixation such as bolt fastening or welding, adhesive bonding has the advantages of being simpler and more convenient, uniform force, reliable performance, beautiful appearance, and a wider range of adaptability.

[0003] Before the 20th century, adhesives were made from natural materials, which could not meet the needs of modern economic growth. At the beginning of the 20th century, a new era of adhesives based on synthetic resins was created. In recent years, adhesives have been used more and more widely, and bonding technology has become one of the three major contemporary connection technologies, including bonding, welding and mechanical connection. In the 1950s, with the development of military, structural parts of aircraft, missiles, spacecraft, etc. all required adhesives that could work for a long time under high temperature loading conditions. In order to meet the needs of the aviation and electronics industries, many researchers have begun to develop high temperature resistant adhesives. In recent years, high temperature resistant adhesives have been widely used in technical fields such as aviation, aerospace, electronics, automobiles, machinery manufacturing, light industry, military industry and construction. A large number of high-temperature resistant adhesives are needed in aerospace technology. For example, supersonic aircraft require adhesives that can be used continuously for 50 kh at 230°C, and aircraft exhaust pipes require adhesives that can withstand high temperatures of 450-700°C. The microelectronics industry requires adhesives that can withstand temperatures above 300°C. Adhesives used in missiles are required to be maintained at 540°C for one minute. Summary of the invention

[0004] The object of the present invention is to provide a wear-resistant adhesive and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a wear-resistant adhesive, which is prepared by using organic silicone resin as colloid, adding modified alumina, modified silica, curing agent, and reinforcing agent, and then treating with plasma and composite silane coupling agent.

[0006] Furthermore, the modified alumina and modified silica are prepared by modifying fumed alumina and fumed silica respectively with 4-phenylbutyltrimethoxysilane.

[0007] Furthermore, the curing agent is specifically polysilazane and silicate.

[0008] Furthermore, the reinforcing agent is specifically titanium powder and boron carbide.

[0009] Furthermore, a method for preparing a wear-resistant adhesive comprises the following preparation steps:

[0010] (1) Mix fumed silica and anhydrous ethanol aqueous solution, wherein the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the solution pH to 4-5 with hydrochloric acid, perform ultrasound at 21 kHz for 25-50 min, add 4-phenylbutyltrimethoxysilane, raise the temperature to 60-80° C., stir at 50-120 rpm for 8-15 h, filter, take the solid, wash it with anhydrous ethanol for 3-5 times, dry it at 55-90° C. for 4-7 h, and prepare fumed alumina by the same method to obtain modified silica and modified alumina;

[0011] (2) Mixing silicone resin, polysilazane, 38 wt% sodium silicate aqueous solution, and dibutyltin dilaurate, heating to 65-85° C., stirring at 30-80 rpm for 1-2 h, adding modified silicon dioxide and modified aluminum oxide, continuing to stir for 2 h, adding titanium powder and boron carbide, ultrasonicating at 21 kHz for 20-40 min, pouring into a mold, and curing at 60-100° C. for 3-7 h to obtain a colloid;

[0012] (3) The colloid was washed with deionized water and acetone three times respectively, dried naturally, and then subjected to plasma treatment. 2 Apply the composite coupling agent and dry it naturally to obtain a wear-resistant adhesive.

[0013] Furthermore, the mass ratio of the fumed silica, anhydrous ethanol aqueous solution and 4-phenylbutyltrimethoxysilane in step (1) is 8-13:300:1.5-2.7.

[0014] Furthermore, the preparation method of the organic silicone resin in step (2) is as follows: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 500-1000 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.1-0.3 times the mass of toluene), and octamethylcyclotetrasiloxane (0.1-0.3 times the mass of toluene) are added dropwise at 0.3-0.6 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7-8 with sodium hydroxide, and then the solvent is removed under reduced pressure at 60-80° C. for 100-200 min, and then the temperature is raised to 130-150° C. and the pressure is reduced and combined for 50-90 min to obtain the product.

[0015] Furthermore, in step (2), the mass ratio of the silicone resin, polysilazane, 38 wt% sodium silicate aqueous solution, dibutyltin dilaurate, modified silicon dioxide, modified aluminum oxide, titanium powder, and boron carbide is 100:10:15:1-2:2-5:2-5:10-30:20-50.

[0016] Furthermore, the process parameters of the plasma in step (3) are: atmosphere is oxygen, vacuum degree is 12.5 Pa, power is 95-127 W, and time is 50-200 s.

[0017] Furthermore, the composite coupling agent in step (3) is prepared by mixing anhydrous ethanol, KH560, KH570, and deionized water in a mass ratio of 7:1:1.5:0.9.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The adhesive of the invention is prepared by using organic silicon resin as colloid, adding modified alumina, modified silicon dioxide, curing agent and reinforcing agent, and then being treated by plasma and composite silane coupling agent to achieve the effects of high temperature resistance and high bonding strength.

[0020] First, 4-phenylbutyltrimethoxysilane is used to interact with the hydroxyl groups on the surfaces of alumina and silica to modify and adsorb on the surfaces of fumed alumina and fumed silica, respectively, thereby enhancing the hydrophobicity of both. Then, it is dispersed in a silicone resin colloid. Since the 4-phenylbutyl chain segment in 4-phenylbutyltrimethoxysilane is relatively long, the contact area with the surfaces of alumina and silica is large, which enhances the lipophilicity of the surfaces of the two, and enables them to be evenly dispersed in the matrix. At the same time, the chemical bonding force between alumina and silica and the silicone resin is enhanced, thereby increasing the intermolecular Then, polysilazane and silicate are used as curing agents for the colloid. The silanol group in polysilazane can react with the silanol group in the silicone resin to produce cross-linking, and eliminate the "unbuttoning" degradation caused by the terminal hydroxyl group, thereby improving the heat resistance of the silicone resin. In this process, silicate cross-links with silica and alumina to form network structures such as silica-silicon and silica-alumina, thereby promoting the curing of the resin colloid. At the same time, alumina and silica will form a stable mullite structure under high temperature conditions, further improving the high temperature resistance and bonding strength of the colloid.

[0021] Secondly, titanium and boron carbide mixed powders are used as reinforcing agents. When subjected to energy impact, the external load is absorbed through the plastic deformation of titanium. This is due to the interaction between the toughening phase and the crack, which causes the crack to shift or deflect at the particle, thereby consuming the energy at the crack tip, thereby achieving the purpose of reinforcement. The surface of the titanium powder will chemically react with the alkaline silicate to promote the curing of the adhesive, thereby making the bonding effect of the adhesive interface better. The spherical particles of gas-phase alumina can also deflect the cracks of the adhesive, thereby consuming more energy and allowing the adhesive to maintain a complete structure, which is beneficial to the improvement of the mechanical properties of the colloid. Among them, boron carbide will oxidize and increase weight at high temperature, accompanied by volume expansion, forming boron oxide with certain wettability and fluidity, which enters the crack pores of the adhesive, reduces the defective holes of the adhesive, and effectively inhibits the high-temperature cracking of silicone resin. The volume shrinks drastically to form a dense adhesive structure. In this process, the silicone resin decomposes into amorphous phases of silicon dioxide and silicon oxycarbide, which react with boron oxide to form a glass phase. As the temperature rises, the diffusion is strengthened, so that more chemical bonds are formed at the interface, thereby greatly improving the bonding strength of the interface. Next, the colloid is treated with plasma and then immersed in a composite silane coupling agent. Since a large number of polar groups are generated on the surface of the silica gel during plasma treatment, the coupling agent can quickly spread and wet on its surface. Moreover, when polar materials are exposed to the atmosphere, some water molecules are always adsorbed on their surfaces. Once the coupling agent surface is wetted, the groups at both ends of the molecule diffuse to the surface with similar polarity respectively. Some groups undergo co-hydrolysis and condensation with the water molecules on the oriented surface or the silanol groups on the surface of the silicone adhesive to produce chemical crosslinking and form chemical bonds, thereby enhancing the adhesion between the colloid and the substrate. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the wear-resistant adhesives prepared in the following examples are as follows:

[0024] The bonding surface of the tinplate sheet was polished with 150-mesh sandpaper for 8 minutes, and then ultrasonically cleaned with anhydrous ethanol and naturally dried. The wear-resistant adhesive was bonded to the treated tinplate sheet and cured at 80°C for 2 hours to obtain the sample.

[0025] Mechanical properties: The same size of the embodiment and the comparative example were measured on a universal electronic tensile testing machine according to GB / T528 for tensile strength and elongation at break.

[0026] Adhesion performance: The adhesion strength of the samples of the embodiment and the comparative example of the same size was tested according to GB / T11211; the adhesion strength of the samples was tested again after being kept at 700°C for 60 minutes.

[0027] Example 1

[0028] (1) Mix fumed silica and anhydrous ethanol aqueous solution, wherein the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the solution pH to 4 with hydrochloric acid, perform ultrasound at 21 kHz for 25 min, add 4-phenylbutyltrimethoxysilane, raise the temperature to 60° C., stir at 50 rpm for 8 h, filter, take the solid, wash it 3 times with anhydrous ethanol, and dry it at 55° C. for 4 h. Prepare fumed alumina by the same method to obtain modified silica and modified alumina; the mass ratio of the fumed silica, anhydrous ethanol aqueous solution, and 4-phenylbutyltrimethoxysilane is 8:300:1.5;

[0029] (2) Deionized water and toluene were mixed in a mass ratio of 1.5:1.8, and under stirring at 500 rpm, 0.1 times the mass of toluene of phenyltrichlorosilane, 0.1 times the mass of toluene of hexamethyldisiloxane, and 0.1 times the mass of toluene of octamethylcyclotetrasiloxane were added dropwise at a rate of 0.3 mL / s, and the water layer was removed by standing, and the pH of the solution was adjusted to 7 with sodium hydroxide, and then the solvent was removed under reduced pressure at 60° C. for 100 minutes, and then the temperature was raised to 130° C. and the pressure was reduced and combined for 50 minutes to obtain an organic silicone resin; the organic silicone resin and polysilazane were added dropwise at a rate of 0.3 mL / s, and ... , 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate are mixed, the temperature is raised to 65°C, stirred at 30rpm for 1h, modified silica and modified alumina are added, stirring is continued for 2h, titanium powder and boron carbide are added, ultrasonicated at 21kHz for 20min, poured into a mold, and cured at 60°C for 3h to obtain a colloid; the mass ratio of the silicone resin, polysilazane, 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate, modified silica, modified alumina, titanium powder, and boron carbide is 100:10:15:1:2:2:10:20;

[0030] (3) Anhydrous ethanol, KH560, KH570, and deionized water were mixed in a mass ratio of 7:1:1.5:0.9 to obtain a composite coupling agent; the colloid was washed with deionized water and acetone three times respectively, dried naturally, and then subjected to plasma treatment. The process parameters were: oxygen atmosphere, vacuum degree of 12.5 Pa, power of 95 W, time of 50 s, and then 8 mL / m 2 Apply the composite coupling agent and dry it naturally to obtain a wear-resistant adhesive.

[0031] Example 2

[0032] (1) Mix fumed silica and anhydrous ethanol aqueous solution, wherein the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the pH value of the solution to 4.5 with hydrochloric acid, perform ultrasound at 21 kHz for 40 min, add 4-phenylbutyltrimethoxysilane, raise the temperature to 70° C., stir at 90 rpm for 11 h, filter, take the solid, wash it 4 times with anhydrous ethanol, and dry it at 70° C. for 5 h. Prepare fumed alumina by the same method to obtain modified silica and modified alumina; the mass ratio of the fumed silica, anhydrous ethanol aqueous solution, and 4-phenylbutyltrimethoxysilane is 11:300:2.2;

[0033] (2) deionized water and toluene were mixed in a mass ratio of 1.5:1.8, and under stirring at 700 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.2 times the mass of toluene), and octamethylcyclotetrasiloxane (0.2 times the mass of toluene) were added dropwise at a rate of 0.4 mL / s, respectively, and the water layer was removed by standing, and the pH of the solution was adjusted to 7.5 with sodium hydroxide, and then the solvent was removed under reduced pressure at 70° C. for 150 min, and then the temperature was raised to 140° C. and the pressure was reduced and combined for 70 min to obtain an organic silicone resin; the organic silicone resin, polysilazane, A 38wt% sodium silicate aqueous solution and dibutyltin dilaurate are mixed, heated to 75°C, stirred at 50rpm for 1.5h, modified silica and modified alumina are added, stirring is continued for 2h, titanium powder and boron carbide are added, ultrasonicated at 21kHz for 30min, poured into a mold, and cured at 80°C for 5h to obtain a colloid; the mass ratio of the silicone resin, polysilazane, 38wt% sodium silicate aqueous solution, dibutyltin dilaurate, modified silica, modified alumina, titanium powder, and boron carbide is 100:10:15:1.4:3:3:16:35;

[0034] (3) Anhydrous ethanol, KH560, KH570, and deionized water were mixed in a mass ratio of 7:1:1.5:0.9 to obtain a composite coupling agent; the colloid was washed with deionized water and acetone three times respectively, dried naturally, and then subjected to plasma treatment. The process parameters were: oxygen atmosphere, vacuum degree of 12.5 Pa, power of 113 W, time of 178 s, and then 12 mL / m 2 Apply the composite coupling agent and dry it naturally to obtain a wear-resistant adhesive.

[0035] Example 3

[0036] (1) Mix fumed silica and anhydrous ethanol aqueous solution, wherein the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the solution pH to 5 with hydrochloric acid, perform ultrasound at 21 kHz for 50 min, add 4-phenylbutyltrimethoxysilane, raise the temperature to 80° C., stir at 120 rpm for 15 h, filter, take the solid, wash it with anhydrous ethanol for 5 times, and dry it at 90° C. for 7 h. Prepare fumed alumina by the same method to obtain modified silica and modified alumina; the mass ratio of the fumed silica, anhydrous ethanol aqueous solution, and 4-phenylbutyltrimethoxysilane is 13:300:2.7;

[0037] (2) Deionized water and toluene were mixed in a mass ratio of 1.5:1.8, and under stirring at 1000 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.3 times the mass of toluene), and octamethylcyclotetrasiloxane (0.3 times the mass of toluene) were added dropwise at a rate of 0.6 mL / s, respectively, and the water layer was removed by standing, and the pH of the solution was adjusted to 8 with sodium hydroxide, and then the solvent was removed under reduced pressure at 80° C. for 200 min, and then the temperature was raised to 150° C. and the pressure was reduced and combined for 90 min to obtain an organic silicone resin; the organic silicone resin and polysilazane were added to the mixture, and ... , 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate are mixed, the temperature is raised to 85°C, stirred at 80rpm for 2h, modified silica and modified alumina are added, stirring is continued for 2h, titanium powder and boron carbide are added, 21kHz ultrasound is applied for 40min, poured into a mold, and cured at 100°C for 7h to obtain a colloid; the mass ratio of the silicone resin, polysilazane, 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate, modified silica, modified alumina, titanium powder, and boron carbide is 100:10:15:2:5:5:30:50;

[0038] (3) Anhydrous ethanol, KH560, KH570, and deionized water were mixed in a mass ratio of 7:1:1.5:0.9 to obtain a composite coupling agent; the colloid was washed with deionized water and acetone three times respectively, dried naturally, and then subjected to plasma treatment. The process parameters were: oxygen atmosphere, vacuum degree of 12.5 Pa, power of 127 W, time of 200 s, and then 16 mL / m 2 Apply the composite coupling agent and dry it naturally to obtain a wear-resistant adhesive.

[0039] Comparative Example 1

[0040] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.

[0041] Comparative Example 2

[0042] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: mix fumed silica and anhydrous ethanol aqueous solution, the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the pH of the solution to 4.5 with hydrochloric acid, ultrasonicate at 21kHz for 40min, add 4-phenylbutyltrimethoxysilane, heat to 70°C, stir at 90rpm for 11h, filter, take the solid, wash it 4 times with anhydrous ethanol, and dry it at 70°C for 5h to obtain modified silica; the mass ratio of the fumed silica, anhydrous ethanol aqueous solution and 4-phenylbutyltrimethoxysilane is 11:300:2.2; the remaining steps are the same as Example 2.

[0043] Comparative Example 3

[0044] The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: mix gas-phase alumina and anhydrous ethanol aqueous solution, the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the pH of the solution to 4.5 with hydrochloric acid, ultrasonicate at 21kHz for 40min, add 4-phenylbutyltrimethoxysilane, heat to 70°C, stir at 90rpm for 11h, filter, take the solid, wash it 4 times with anhydrous ethanol, and dry it at 70°C for 5h to obtain modified alumina; the mass ratio of the gas-phase alumina, anhydrous ethanol aqueous solution and 4-phenylbutyltrimethoxysilane is 11:300:2.2; the remaining steps are the same as Example 2.

[0045] Comparative Example 4

[0046] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 700 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.2 times the mass of toluene), and octamethylcyclotetrasiloxane (0.2 times the mass of toluene) are added dropwise at 0.4 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7.5 with sodium hydroxide, and then the solvent is removed under reduced pressure at 70° C. for 150 min, and then the temperature is raised to 140° C. and the pressure is reduced and combined for 70 min to obtain an organic Silicone resin; mix silicone resin, 38wt% sodium silicate aqueous solution and dibutyl tin dilaurate, heat to 75°C, stir at 50rpm for 1.5h, add modified silica and modified alumina, continue stirring for 2h, add titanium powder and boron carbide, ultrasonicate at 21kHz for 30min, pour into a mold, and cure at 80°C for 5h to obtain a colloid; the mass ratio of the silicone resin, 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate, modified silica, modified alumina, titanium powder and boron carbide is 100:15:1.4:3:3:16:35; the remaining steps are the same as those in Example 2.

[0047] Comparative Example 5

[0048] The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 700 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.2 times the mass of toluene), and octamethylcyclotetrasiloxane (0.2 times the mass of toluene) are added dropwise at 0.4 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7.5 with sodium hydroxide, and then the solvent is removed under reduced pressure at 70° C. for 150 min, and then the temperature is raised to 140° C. and the pressure is reduced for 70 min. min to obtain an organosilicon resin; mix the organosilicon resin, polysilazane and dibutyl tin dilaurate, heat to 75°C, stir at 50rpm for 1.5h, add modified silica and modified alumina, continue stirring for 2h, add titanium powder and boron carbide, ultrasonicate at 21kHz for 30min, pour into a mold, and cure at 80°C for 5h to obtain a colloid; the mass ratio of the organosilicon resin, polysilazane, dibutyl tin dilaurate, modified silica, modified alumina, titanium powder and boron carbide is 100:10:1.4:3:3:16:35; the remaining steps are the same as those in Example 2.

[0049] Comparative Example 6

[0050] The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 700 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.2 times the mass of toluene), and octamethylcyclotetrasiloxane (0.2 times the mass of toluene) are added dropwise at 0.4 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7.5 with sodium hydroxide, and then the solvent is removed under reduced pressure at 70° C. for 150 min, and then the temperature is raised to 140° C. and the pressure is reduced and combined for 70 min to obtain an organosilicon resin. Fat; mix an organosilicon resin, polysilazane, a 38wt% aqueous sodium silicate solution, and dibutyl tin dilaurate, heat to 75°C, stir at 50rpm for 1.5h, add modified silica and modified alumina, continue stirring for 2h, add boron carbide, ultrasonicate at 21kHz for 30min, pour into a mold, and cure at 80°C for 5h to obtain a colloid; the mass ratio of the organosilicon resin, polysilazane, 38wt% aqueous sodium silicate solution, dibutyl tin dilaurate, modified silica, modified alumina, and boron carbide is 100:10:15:1.4:3:3:35; the remaining steps are the same as in Example 2.

[0051] Comparative Example 7

[0052] The difference between Comparative Example 7 and Example 2 is that step (2) is different. Step (2) is changed to: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 700 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.2 times the mass of toluene), and octamethylcyclotetrasiloxane (0.2 times the mass of toluene) are added dropwise at 0.4 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7.5 with sodium hydroxide, and then the solvent is removed under reduced pressure at 70° C. for 150 min, and then the temperature is raised to 140° C. and the pressure is reduced and combined for 70 min to obtain organic silicon. Resin; mix silicone resin, polysilazane, 38wt% sodium silicate aqueous solution, and dibutyl tin dilaurate, heat to 75°C, stir at 50rpm for 1.5h, add modified silica and modified alumina, continue stirring for 2h, add titanium powder, ultrasonicate at 21kHz for 30min, pour into a mold, and cure at 80°C for 5h to obtain a colloid; the mass ratio of the silicone resin, polysilazane, 38wt% sodium silicate aqueous solution, dibutyl tin dilaurate, modified silica, modified alumina, and titanium powder is 100:10:15:1.4:3:3:16; the remaining steps are the same as Example 2.

[0053] Comparative Example 8

[0054] The difference between Comparative Example 8 and Example 2 is that step (3) is different. Step (3) is changed to: anhydrous ethanol, KH560, KH570, and deionized water are mixed in a mass ratio of 7:1:1.5:0.9 to obtain a composite coupling agent; the colloid is washed with deionized water and acetone three times respectively, dried naturally, and heated at 12 mL / m 2 Apply the composite coupling agent and dry naturally to obtain the wear-resistant adhesive; the remaining steps are the same as those in Example 2.

[0055] Comparative Example 9

[0056] The difference between Comparative Example 9 and Example 2 is that step (3) is different. Step (3) is changed to: the colloid is washed with deionized water and acetone three times respectively, dried naturally, and plasma treated. The process parameters are: atmosphere is oxygen, vacuum degree is 12.5 Pa, power is 113 W, time is 178 s, and a wear-resistant adhesive is obtained; the remaining steps are the same as Example 2.

[0057] Comparative Example 10

[0058] The difference between Comparative Example 10 and Example 2 is that there is no step (3); the remaining steps are the same as Example 2.

[0059] Effect example

[0060] Table 1 below shows the performance analysis results of the wear-resistant adhesives of Examples 1 to 3 of the present invention and Comparative Examples 1 to 10.

[0061] Table 1

[0062]

[0063]

[0064] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses 4-phenylbutyltrimethoxysilane to modify the surface of fumed alumina and fumed silica, and then disperses them in the silicone resin colloid. The 4-phenylbutyl segment in the 4-phenylbutyltrimethoxysilane is relatively long, and the contact area with the surface of alumina and silica is large, so that the lipophilicity of the surfaces of the two is enhanced, and they can be evenly dispersed in the matrix, and at the same time, the chemical bond strength between alumina and silica and the silicone resin is enhanced, thereby improving the high temperature resistance and bonding strength of the matrix. Then, polysilazane and silicate are used as As the curing agent of the colloid, the silanol group in polysilazane can react with the silanol group in the silicone resin to produce cross-linking, and eliminate the "unbuttoning" degradation caused by the terminal hydroxyl group, so as to improve the heat resistance of the silicone resin. In this process, the silicate cross-links with silicon dioxide and aluminum oxide to form a network structure such as silicon-oxygen-silicon and silicon-oxygen-aluminum, thereby promoting the curing of the resin colloid. At the same time, aluminum oxide and silicon dioxide will form a stable mullite structure under high temperature conditions, further improving the high temperature resistance and bonding strength of the colloid. Titanium and boron carbide mixed powder is used as a reinforcing agent. When subjected to energy impact, the plastic deformation of titanium To absorb the external load, and then consume the energy of the crack tip, so as to achieve the purpose of strengthening, and the surface of the titanium powder will react chemically with the alkaline silicate to promote the curing of the adhesive. The spherical particles of gas-phase alumina can also deflect the cracks of the adhesive, so that the adhesive can maintain a complete structure, which is beneficial to the improvement of the mechanical properties of the colloid. Among them, boron carbide will oxidize and increase weight at high temperature, and form boron oxide with certain wettability and fluidity, which will enter the crack pores of the adhesive to form a dense adhesive structure. In this process, the silicone resin decomposes silicon dioxide and The amorphous phase of silicon carbide reacts with boron oxide to form a glass phase, thereby greatly improving the bonding strength of the interface. Next, the colloid is treated with plasma and then immersed in a composite silane coupling agent. Since a large number of polar groups are generated on the surface of the silica gel during the plasma treatment, the coupling agent can quickly spread and wet the surface. The groups at both ends of the molecule diffuse to the surface with similar polarity respectively. Some groups undergo co-hydrolysis and condensation with the water molecules on the oriented surface or the silanol groups on the surface of the organic silicone adhesive to produce chemical crosslinking and form chemical bonds, thereby enhancing the adhesion between the colloid and the substrate.

[0065] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A wear-resistant adhesive, characterized in that: The wear-resistant adhesive is prepared by taking organic silicon resin as colloid, adding modified aluminum oxide, modified silicon dioxide, curing agent and reinforcing agent, and then treating with plasma and composite silane coupling agent.

2. A wear-resistant adhesive according to claim 1, characterized in that: The modified alumina and modified silica are prepared by respectively modifying fumed alumina and fumed silica with 4-phenylbutyltrimethoxysilane.

3. A wear-resistant adhesive according to claim 1, characterized in that: The curing agent is specifically polysilazane and silicate.

4. The wear-resistant adhesive according to claim 1, characterized in that: The reinforcing agent is specifically titanium powder and boron carbide.

5. A method for preparing a wear-resistant adhesive, characterized in that: The method comprises the following preparation steps: (1) Mix fumed silica and anhydrous ethanol aqueous solution, wherein the mass ratio of anhydrous ethanol to deionized water is 3:1, adjust the solution pH to 4-5 with hydrochloric acid, perform ultrasound at 21 kHz for 25-50 min, add 4-phenylbutyltrimethoxysilane, raise the temperature to 60-80° C., stir at 50-120 rpm for 8-15 h, filter, take the solid, wash it with anhydrous ethanol for 3-5 times, dry it at 55-90° C. for 4-7 h, and prepare fumed alumina by the same method to obtain modified silica and modified alumina; (2) Mixing silicone resin, polysilazane, 38 wt% sodium silicate aqueous solution, and dibutyltin dilaurate, heating to 65-85° C., stirring at 30-80 rpm for 1-2 h, adding modified silicon dioxide and modified aluminum oxide, continuing to stir for 2 h, adding titanium powder and boron carbide, ultrasonicating at 21 kHz for 20-40 min, pouring into a mold, and curing at 60-100° C. for 3-7 h to obtain a colloid; (3) The colloid was washed with deionized water and acetone three times respectively, dried naturally, and then subjected to plasma treatment. 2 Apply the composite coupling agent and dry it naturally to obtain a wear-resistant adhesive.

6. The method for preparing a wear-resistant adhesive according to claim 5, characterized in that: The mass ratio of the fumed silica, anhydrous ethanol aqueous solution and 4-phenylbutyltrimethoxysilane in step (1) is 8-13:300:1.5-2.

7.

7. The method for preparing a wear-resistant adhesive according to claim 5, characterized in that: The preparation method of the organic silicone resin in step (2) is as follows: deionized water and toluene are mixed in a mass ratio of 1.5:1.8, and under stirring at 500-1000 rpm, phenyltrichlorosilane (0.1 times the mass of toluene), hexamethyldisiloxane (0.1-0.3 times the mass of toluene), and octamethylcyclotetrasiloxane (0.1-0.3 times the mass of toluene) are added dropwise at 0.3-0.6 mL / s, respectively, and the water layer is removed by standing, and the pH of the solution is adjusted to 7-8 with sodium hydroxide, and then the solvent is removed under reduced pressure at 60-80° C. for 100-200 min, and then the temperature is raised to 130-150° C. and the pressure is reduced and combined for 50-90 min to obtain the product.

8. The method for preparing a wear-resistant adhesive according to claim 5, characterized in that: The mass ratio of the organosilicon resin, polysilazane, 38wt% sodium silicate aqueous solution, dibutyltin dilaurate, modified silicon dioxide, modified aluminum oxide, titanium powder and boron carbide in step (2) is 100:10:15:1-2:2-5:2-5:10-30:20-50.

9. The method for preparing a wear-resistant adhesive according to claim 5, characterized in that: The process parameters of the plasma in step (3) are: atmosphere is oxygen, vacuum degree is 12.5 Pa, power is 95-127 W, and time is 50-200 s.

10. The method for preparing a wear-resistant adhesive according to claim 5, characterized in that: The composite coupling agent in step (3) is prepared by mixing anhydrous ethanol, KH560, KH570 and deionized water in a mass ratio of 7:1:1.5:0.9.